Evolution of Acquired Drug Resistance in BRAF-Mutant Melanoma - Josué Ballesteros-Álvarez; Ana M. Blázquez-Medela (DNA)
Melanoma is a highly aggressive type of skin cancer. Metastatic melanoma tumors have historically featured a particularly poor prognosis and have often been considered incurable. Recent advances in targeted therapeutic interventions have radically changed the landscape in metastatic melanoma management, significantly increasing the overall survival of patients. Hyperactive BRAF is the most common mutational event found in metastatic melanoma and its inhibition has proven to be a successful approach in a number of patients. Unfortunately, initial tumor retreat is followed by relapse in most cases, highlighting the elusiveness of finding a widely effective treatment. Melanoma tumors often carry a particularly high number of mutations in what is known as a high level of inter- and intra-patient tumor heterogeneity, driving resistance to treatment. The various mutations that are present in these tumors, in addition to impacting the root cause of the malignancy and the potential for therapeutic interventions, have also been known to arise during tumor clonal evolution leading to the establishment of drug resistance, a major issue in melanoma management.